LEGAL RESEARCH: AN OVERVIEW OF A RESEARCH PROPOSAL - O. J. Jejelola (European Scientific Journal, ESJ, 2014)
The writer looked at the problems involved in writing a legal research proposal by identifying some of the basic challenges such as the choice of topic, resource materials, methodology and the theoretical framework to be adopted for the research. The aim is to take a holistic overview of a legal research methodology. The primary and secondary sources of material selection were used through the use of the law libraries and the internet as well as journals and periodicals to gather information for this study. The study shows that legal research works are still much being conducted under the doctrinal method which is not empirical in view of the fact that analysis of statistical data or qualitative methodology is often viewed as the concern of the pure scientist rather than in the humanities. In conclusion, it was observed and recommended that the need to embark on empirical legal research methodology cannot be over emphasized as it is the only panacea by which the sociological effect of the law could be attained in the 21st century.